Twentieth-Century Drawings : Selections from the Whitney Museum of American Art - Whitney Museum of American Art, New York (New York : Dover Publications Inc., 1981)
Albers, Josef ; Albright, Ivan Le Lorraine ; Bacon, Peggy ; Barnes, Robert ; Baskin, Leonard ; Baziotes, William ; Beauchamp, Robert ; Benton, Thomas Hart ; Bishop, Isabel ; Bochner, Mel ; Bontecou, Lee ; Brainard, Joe ; Burchfield, Charles ; Cadmus, Paul ; Calder, Alexander ; etc.
Twentieth-Century Drawings : Selections from the Whitney Museum of American Art, Whitney Museum of American Art, New York, 1981
boek